Peran Sumber Daya Manusia dalam Mengembangkan Inovasi Kewirausahaan di Era Disrupsi: Studi pada Lembaga Dakwah Majelis Ulama Indonesia (MUI) - Dinda Luthfiaturrahmah Alhaq; Cecep Castrawijaya (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This article discusses the role of human resources (HR) in dakwah institutions in developing entrepreneurial innovation in the era of disruption, with a focus on the Indonesian Ulema Council (MUI) as a case study. The development of digital technology demands that dakwah institutions transform from traditional patterns toward adaptive, creative, and economically empowering approaches. This study uses a qualitative method with a descriptive-analytical library research approach. The results of the analysis show that HR plays a strategic role as the driving force of dakwah innovation and entrepreneurship based on Islamic values. Adaptive and creative human resources with strong digital literacy are able to bridge dakwah activities with productive economic initiatives, such as sharia entrepreneurship training, Islamic financial literacy, and the development of halal certification. MUI has demonstrated the integration of dakwah, innovation, and digital technology as a response to the dynamics of the disruption era. Therefore, strengthening HR capacity is a key factor for dakwah institutions in creating a model of dakwah that is relevant, competitive, and oriented toward the welfare of the ummah.